2014
DOI: 10.1111/ejss.12153
|View full text |Cite
|
Sign up to set email alerts
|

Regional‐scale characterization of the geomorphic control of the spatial distribution of soil organic carbon in cropland

Abstract: The heterogeneity of the spatial distribution of soil organic carbon (SOC) at the landscape scale is generally not considered in regional or national SOC dynamics models. In cropland this heterogeneity is controlled largely by topography, which influences the distribution of water, energy and sediments, and thus the SOC dynamics. Sediment redistribution rates have increased strongly since the mechanization of agriculture. The over-simplification of landscape processes in regional models of C dynamics may add t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…This finding is logical since in the mountains there are relatively many shallow soils and the topography is highly variable. These findings confirm the relation between SOC and topography‐dominated landscapes, which was previously demonstrated by, e.g., Stevens et al []. In addition, a high evapotranspiration and low sand content are important for explaining the subsoil carbon (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…This finding is logical since in the mountains there are relatively many shallow soils and the topography is highly variable. These findings confirm the relation between SOC and topography‐dominated landscapes, which was previously demonstrated by, e.g., Stevens et al []. In addition, a high evapotranspiration and low sand content are important for explaining the subsoil carbon (Figure ).…”
Section: Resultssupporting
confidence: 90%
“…Additionally, the DEM data with a resolution of 10m was obtained from aerial imageries and used to extract landform, hydrological, and spatial indices. The topography was classified using the approaches described in FAO guidelines for soil description [62]. Additional landform characteristics of the study area was described using different landscape metrics including slope, relief, curvature, TWI, TPI, and others.…”
Section: Data Sources Software and Extraction Of Environmental Covamentioning
confidence: 99%
“…Field boundaries may also coincide with landscape features (e.g., hedges, streams, mounds) that have an influence on SOC by preventing lateral transport of sediments and SOC between adjacent fields (see for example Viaud et al, 2010;Ghariani et al, 2014). The presence of a field effect may explain the difficulty of Stevens et al (2014) to efficiently predict topsoil SOC (in an area of homogeneous texture) using only topographic information (terrain attributes). Doetterl et al (2013) also showed that, within our study area, the topography became a good predictor of SOC only for the subsoil at depths below 20 cm, where the influence of field-related processes was expected to be weaker.…”
Section: Rigorous Assessment Of Texture and Fields Effectmentioning
confidence: 99%